1997
DOI: 10.1007/s004649900365
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of laparoscopic surgery in the diagnosis and treatment of peritonitis

Abstract: Laparoscopic surgery is safe and very efficient in the diagnosis and treatment of patients with peritonitis. In most instances a definitive treatment can be carried out without conversion and has the additional and well-known advantages of minimally invasive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
1
24
0
2
Order By: Relevance
“…Some authors have questioned whether the pneumoperitoneum might facilitate the progression of peritonitis by causing its dissemination in the abdominal cavity, thus increasing the risk of bacteremia and shock [18,19]. However, several clinical studies have demonstrated that there is no increase in infectious morbidity in patients who undergo a laparoscopic operation for peritonitis vs those who have compared with open surgery [3,5]. Moreover, clinical and experimental investigations have shown that laparoscopic surgery maintains its advantages in a septic environment [1,12].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have questioned whether the pneumoperitoneum might facilitate the progression of peritonitis by causing its dissemination in the abdominal cavity, thus increasing the risk of bacteremia and shock [18,19]. However, several clinical studies have demonstrated that there is no increase in infectious morbidity in patients who undergo a laparoscopic operation for peritonitis vs those who have compared with open surgery [3,5]. Moreover, clinical and experimental investigations have shown that laparoscopic surgery maintains its advantages in a septic environment [1,12].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies, 10,20,22,23 including this study, suggest that there is no increase in morbidity and mortality after laparoscopic management of patients with peritonitis. Anastomotic leakage after laparoscopic proctectomy can be managed with minimally invasive surgery if it can be diagnosed earlier, thus the incidence of laparotomy for anastomotic leakage is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic surgery has been reported to be effective treatment for intra-abdominal inflammatory disease, including acute appendicitis [4][5][6], diverticular disease [7], and perforated peptic ulcer [8,9]. Furthermore, these techniques are applied in a variety of surgical conditions complicated by peritonitis resulting in intraperitoneal sepsis [7,10,11].…”
Section: Introductionmentioning
confidence: 99%